2017
DOI: 10.1016/j.drugalcdep.2017.05.043
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine dependence modulates the effect of HIV infection on brain activation during intertemporal decision making

Abstract: Background Both HIV infection and chronic cocaine use alter the neural circuitry of decision making, but the interactive effects of these commonly comorbid conditions have not been adequately examined. This study tested how cocaine moderates HIV-related neural activation during an intertemporal decision-making task. Methods The sample included 73 participants who differed on cocaine and HIV status (18 COC+/HIV+, 19 COC+/HIV-, 19 COC-/HIV+, 17 COC-/HIV-). Participants made choices between smaller, sooner and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…Table 1). Finally, while there were few effects during the decision making phase, two studies reported disengagement of the executive network (vlPFC/dlPFC) during high risk or difficult decisions (Kohno et al, 2014; Meade et al, 2017).…”
Section: Resultsmentioning
confidence: 98%
“…Table 1). Finally, while there were few effects during the decision making phase, two studies reported disengagement of the executive network (vlPFC/dlPFC) during high risk or difficult decisions (Kohno et al, 2014; Meade et al, 2017).…”
Section: Resultsmentioning
confidence: 98%
“…This pattern of hyperactivation within task-relevant regions and engagement of additional regions has been interpreted as a compensatory mechanism to preserve cognitive performance in the context of neural injury, which can only be maintained up to a certain level of difficulty (Hakkers et al, 2017). Additional studies focused on cocaine suggest that drug abuse may further exhaust neural resources in HIV+ persons, as evidenced by hypoactivation in task-relevant regions (Meade et al, 2018; Meade et al, 2017; Meyer et al, 2014). However, the effects of marijuana abuse on neural activation patterns have not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…These powerfully addictive stimulant drug molecules have been studied to have an exaggerating effect during HIV infection (Jayant et al, 2017 ). Cocaine (coc), a very common abused drug within PLWH, exerts malicious effects on the CNS (Javadi-Paydar et al, 2017 ; Meade et al, 2017 ; Wakim et al, 2017 ). In the presence of coc, the additive effect of HIV-1 Tat and coc may increase Aβ aggregation, which is a common factor in aging and HIV associated neurological disorders.…”
Section: Introductionmentioning
confidence: 99%